Image Browsing on a Large Display - Hedman, A. (Proceedings of the ITI 2007 : 29th International Conference on Information Technology Interfaces : ITI 2007 : June 25-28, 2007, Cavtat/Dubrovnik, Croatia, 2007)
We conducted a usability study on a 50" plasma display comparing three different browser alternatives (iconic, zoom-and-pan, and bifocal view) for an electronic bulletin board containing thumbnails of notes. For input device we used a 3D mouse. We conducted an experiment where 10 subjects performed browsing tasks with each browser. We found that users performed significantly better with the iconic browser than with the zoom-and-pan-browser. There was no significant difference between the fisheye browser and any of the other two. The users preferred the iconic browser.